OPERATIONALIZING AGRICULTURAL SECURITY: STRENGTHENING NEW MEXICO’S BIOSECURITY AND EMERGENCY READINESS IN ANIMAL AGRICULTURE - Dise, Joshua (My University, 2025)
New Mexico’s expansive livestock industry, active cross-border trade, and shared border with Mexico heighten its vulnerability to foreign animal disease (FAD) outbreaks and mass mortality incidents—events that pose significant threats to animal health, public safety, and economic continuity. This applied research and planning initiative critically evaluates New Mexico’s agricultural preparedness through two key frameworks: the Large Animal Mass Mortality Carcass Management Plan and the Emergency FAD Vaccination Plan. The carcass management plan outlines scalable, environmentally compliant, and biosecure disposal strategies, supported by interagency coordination and clearly defined operational triggers. The vaccination plan guides emergency response through risk-based herd targeting, resource prioritization, practical biosecurity practices, and regulatory integration. These efforts are further contextualized by two commentary articles that expand the discourse on agricultural security: one addressing operational challenges and best practices in carcass disposal, another highlighting biosecurity risks in livestock exhibition settings, and a third advocating for systems-based approaches to agricultural security across both crop and livestock domains. Developed in collaboration with governmental, tribal, industry, and academic stakeholders, this integrated portfolio of planning and scholarship reinforces a systems-thinking approach to agricultural security—advancing proactive risk mitigation, continuity of operations, and resilience in the face of transboundary disease threats.
Keywords: Agricultural security; Carcass management; Emergency vaccination; Foreign animal disease (FAD); Livestock health